Changes in dielectric and ferroelectric properties of Fe3+ / Nb5+ hybrid-doped barium titanate ceramics under compressive stress - M. Unruan (2018)
The influences of compressive stress on the dielectric and ferroelectric properties of Fe3+/ Nb5+hybrid-doped barium titanate (BaTiO3) ceramics were investigated. Superimposed compressive stress had a pronounced effect on the electrical properties of the ceramics. The response of low-field dielectric properties to stress changed from soft to hard piezoelectric behavior with increasing Nb5+content. While ferroelectric properties decreased with stress, hardening behavior was observed with increasing Nb5+content in hybrid-doped BaTiO3ceramics. A mechanism based on induced change in the acceptor valence by the donor dopant in hybrid-doped BaTiO3ceramics was proposed to explain the results obtained. © 2008 American Institute of Physics.